SYNTHESIS, ANALGESIC, ANTI-INFLAMMATORY AND IN VITRO ANTIMICROBIAL STUDIES OF SOME NOVEL SCHIFF AND MANNICH BASE OF 5-SUBSTITUTED ISATIN DERIVATIVES - PRAKASH, CHINNASAMY RAJARAM; Raja, Sundararajan; Saravanan, Govidaraj (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: Synthesis and analgesic, anti-inflammatory and antimicrobial evaluation of some novel Schiff and Mannich bases of isatin derivatives. Methods: A series of novel 3-(4-(2-(substituted benzylideneamino)thiazol-4-yl)phenylimino)-1-((dimethylamino)methyl)-5-fluoroindolin-2-one Schiff and Mannich base derivatives were synthesized by using various aromatic aldehydes with isatin derivatives. The chemical structures of all synthesized compounds were confirmed by IR, 1H-NMR, Mass spectra and elemental analysis. All the synthesized compounds were screened for its analgesic, anti-inflammatory and antimicrobial activity. Results: The results of analgesic, anti-inflammatory and antimicrobial activity showed that some of the synthesized compounds were exhibited promising results. Conclusion: This investigation identified the potent analgesic, anti-inflammatory and anti-microbial agents and these molecules will be subjected to further studies in our laboratory.